PENGUATAN PROFIL PELAJAR PANCASILA MELALUI KEGIATAN EKSTRAKULIKULER DI SMPIT DARUL MUTAQIN PARUNG BOGOR JAWA BARAT - Lisyawati, Elis; Magfiroh, Ita; Olivia, Samantha; Nadia, Nurul; Marwah, Malika; Wardani, Dea Putri (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
The independent curriculum is one of the efforts or tools of the national education system to improve the quality of education in Indonesia. This encourages formal schools, both primary and secondary education, to participate in implementing the P5 programme. SMPIT Darul Mutaqin, which is located in Parung, Bogor Regency, has implemented the Merdeka curriculum since 2021.The purpose of this research is to find out how to optimise extracurricular activities in realising the P5 Pancasila Student Profile. Case study at SMPIT Darul Mutaqin Parung, Bogor Regency. This research uses a qualitative approach and uses an analytical descriptive method. Data collection was carried out through observation, in-depth interviews, and documentation. The informants of this research are the Principal, Head of Curriculum, Curriculum Coordinator, PAI Teacher, and Students. After that, the data was analysed with the stages of data reduction, then data presentation and conclusion drawing. Furthermore, the data were tested for validity through triangulation of sources and techniques.The results showed that the optimisation of extracurricular activities in strengthening the Pancasila student profile (P5) at SMPIT Darul Mutaqin Bogor Regency has been running well. This is evidenced by the implementation of the mustaqili programme and workshops running smoothly, and it is proven that the Pancasila Learner Profile indicators can be well familiarised through assessments carried out formatively and summatively to measure students' attitudes, knowledge, and skills, as well as evaluations by schools and government facilitators to improve the implementation of the Merdeka Curriculum in order to strengthen the Pancasila learner profile through extracurricular activities.